Cultural Considerations in Interprofessional Education: A Scoping Review - Dowell, Sharon; Charnetski, Matt; Tarbet, Amanda; Palaganas, Janice C. (Journal of Research in Interprofessional Practice and Education, 2022)
Background: Global culture influences health behaviors and attitudes and the way we communicate and solve problems; it can also significantly affect the efficiency of the multicultural and interprofessional healthcare team. This scoping review aims to understand and identify global cultural considerations that exist in interprofessional education (IPE) and that influence the development, implementation, and effectiveness of IPE.Methods and Findings: The search included peer-reviewed articles focused on both IPE and global culture, also referred to as national, ethnic, or racial culture. There was no limitation placed on levels of learners nor specific health professions. Articles were excluded if they did not explicitly discuss global cultural considerations in IPE. The authors screened 1094 records, and 155 full-text articleswere assessed for eligibility. No eligible papers were found for inclusion yielding an empty review. The most common reasons for exclusion were failure to address global culture and a focus on provider-patient cultural competency as opposed to cultural aspects of IPE.Conclusions: Despite the recognition of the importance of global culture in all interactions, it is not explicitly addressed within the interprofessional healthcare team or the development and implementation of IPE. Studies addressing culturally congruent teamwork and IPE, and the relationship to culturally inclusive patient care, are needed.